Peningkatan kualitas tanah melalui formulasi sludge industri, arang sekam, dan kompos - Indri Hapsari Fitriyani; Fahrizal Hazrah; Shobrina Muthmainnah Nurdifa (Fakultas Pertanian Universitas Majalengka, 2025)
Industrial wastewater sludge is rich in organic matter and nutrients and has the potential to be used as a amendments despite its high moisture content (91,87%). Rice husk charcoal can address moisture and heavy metal content to achieve quality standards. This study aims to determine the optimal combination of each material and to investigate the correlation between chemical and biological properties. Incubation of the growing medium (sludge, rice husk charcoal, compost) was conducted using seven different material combinations with a completely randomized design. Soil chemical analysis (pH, organic carbon, N, P, K, KTK) and soil biological analysis (total microbes and fungi) were conducted after one month of incubation. The results showed that MSG sludge is nutrient-rich (organic carbon 46.63%, N 7.30%) but Fe (27,836 ppm) and Pb (54 ppm) exceed the limits. Treatment P1 (100% sludge, 75% rice husk charcoal, and 50% compost) had the highest total microorganisms and fungi (0.75 × 10⁵ CFU/g and 0.88 × 10⁵ CFU/g), as well as the highest pH, organic carbon, N, P, K, and KTK. Fe increased while Pb decreased. Treatment P1 was the best combination and met the quality standards for soil conditioners. Microbes and fungi were positively correlated with pH. KTK was positively correlated with pH and organic carbon. An increase in pH had the highest positive correlation with the growth of microbes and fungi.